Documents of the Commissioner of the Fuehrer for the supervision of the entire intellectual and ideological schooling and training of the NSDAP (1934-1945) of Alfred Rosenberg in the Federal Archives of Germany: a source study aspect - Kashevarova Nataliya (Рукописна та книжкова спадщина України, 2022)

(untitled)
The purpose of the research is to characterize the composition and content of the documents of the Commissioner of the Fuehrer for the Supervision of the Entire Intellectual and Ideological Schooling and Training of the NSDAP (here in after - the Rosenberg Office) to determine the place of these documents in the source base of the study of the history of the Third Reich, to analyze their information potential as sources on the history of national socialist ideology and occupation policy. The research methodologyis based on scientific principles of historicism, objectivity, and systematicity, represented by historical-comparative and historical-archival methods, as well as methods of source analysis. The scientific novelty. The documents of the Rosenberg Office as a complete documentary complex have not yet been the subject of scientific research, although some historians have used these documents as sources for the history of National Socialism, A. Rosenberg’s biographical portrait, but they were not considered as sources for the ideological component of the Nazi occupation policy. Conclusions. A brief analysis of the documents of the Rosenberg Office allows us to conclude that these documents are valuable sources for studying the history of the development of the National Socialism ideology and itsinfluence through the NSDAP system. Among them, there are plans, orders, instructions, reflecting objectives and structure of the Rosenberg Office, functionsof its departments, ideological materialson anti-Semitism, Bolshevism, religion, as well as reference materialson National Socialist figures in the field of culture. A special place amongthe documents of the Service is held by materials covering its participation in the ideological training of Wehrmacht officers, as well as biographical sources documents on the activities of the staff of the Rosenberg Office. These documents also reveal its ties with a wide range of ot her Nazi agencies that participated in the process of creating Nazi propaganda.